EFISIENSI DAN EFEKTIVITAS LAYANAN PADA SATUAN PELAYANAN SATU ATAP KOTA BEKASI - Kumiawati Mulyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2007)
The Success of Development Regional Economic Process is depend on how the government apply the task and junction as well. The one indication of regional economic development result and desentralizations is increase of services quality and social welfare, development of democracy, justice, egalitarianism and good relationship between regional and central government. The study have done in Bekasi city especially Satuan Pelayanan Satu Atap the one of government’s institutions. The Study use the Balanced Score Card Analysis especially financial and customers aspect because there’s data limitations.The aim of the study to know about effectiveness and efficiency of public services. Result of the study is describe that the public services is applied effectively and efficiency its shown in financial and consumers aspect.